2020
DOI: 10.1007/s00405-020-05993-x
|View full text |Cite
|
Sign up to set email alerts
|

Recommendation of a practical guideline for safe tracheostomy during the COVID-19 pandemic

Abstract: Purpose The COVID-19 pandemic is placing unprecedented demand upon critical care services for invasive mechanical ventilation. There is current uncertainty regarding the role of tracheostomy for weaning ventilated patients with COVID-19 pneumonia. This is due to a number of factors including prognosis, optimal healthcare resource utilisation, and safety of healthcare workers when performing such a high-risk aerosol-generating procedure. Methods Literature review and proposed practical guideline based on the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
213
0
31

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(257 citation statements)
references
References 28 publications
3
213
0
31
Order By: Relevance
“…Sixty (69.0%) patients had chronic medical illnesses, and the most common illnesses were hypertension (40.0%), coronary heart disease (21.1%), diabetes (17.5%) and cerebrovascular disease (10.0%) ( Table 1). Thirty (37.5%) patients received tracheostomies within 14 days after intubation, and their median duration between intubation and tracheostomy was signi cantly shorter than that of the late tracheostomy group ( [11][12][13][14][15][16][17][18][19][20][21], p = 0.034) at ICU admission and lower APACHE II scores (13 (SD 4) vs 17 (SD 6), p = 0.010) before tracheostomy. Among all 80 patients, lymphocytopenia and hypoalbuminemia at hospital admission and hypoxemia at ICU admission were prominent (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sixty (69.0%) patients had chronic medical illnesses, and the most common illnesses were hypertension (40.0%), coronary heart disease (21.1%), diabetes (17.5%) and cerebrovascular disease (10.0%) ( Table 1). Thirty (37.5%) patients received tracheostomies within 14 days after intubation, and their median duration between intubation and tracheostomy was signi cantly shorter than that of the late tracheostomy group ( [11][12][13][14][15][16][17][18][19][20][21], p = 0.034) at ICU admission and lower APACHE II scores (13 (SD 4) vs 17 (SD 6), p = 0.010) before tracheostomy. Among all 80 patients, lymphocytopenia and hypoalbuminemia at hospital admission and hypoxemia at ICU admission were prominent (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…During the pandemic of COVID-19, it remains unclear whether early tracheostomy performance is bene cial to critically ill COVID-19 patients. Some guidelines [16][17][18] suggested that tracheostomy should be delayed until at least 14 days from endotracheal intubation because viral load in the upper and lower airway may be high in the early course of the infection in COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Postoperative care represents another open issue that should be explored in the next few months, based on gradually evolving body of available data. 3,4 In our experience, circuit disconnections were strictly avoided, and only closed in-line suctioning was used.…”
Section: Discussionmentioning
confidence: 96%
“…Data are limited regarding the proportion of mechanically ventilated COVID-19 positive patients requiring tracheostomy but preliminary data including that from our own tertiary institution suggests a range between <10%-19.3%, [9,10]. Most published guidelines have recommended late tracheostomy to minimise the risk of disease transmission [11,12].…”
Section: Introductionmentioning
confidence: 99%